General Phenotype of NADase Induction by CLI Treatment in Streptococcus pyogenes - Tatsuno, Ichiro; Isaka, Masanori; Hasegawa, Tadao (International Journal of Microbiology, 2022)
The administration of high-dose clindamycin (CLI) along with penicillin is recommended for the treatment of streptococcal toxic-shock syndrome (STSS). However, we previously reported that a “subinhibitory dose” of CLI induced the expression of the NAD-glycohydrolase (NADase) exotoxin in an emm1-type Streptococcus pyogenes 1529 strain isolated from an STSS patient. In this study, we examine NADase induction by CLI treatment using an extracellular NADase activity assay instead of the previous two-dimensional gel electrophoresis assay. The examination revealed that CLI administration can induce NADase expression in a dose-dependent manner. We analyzed 23 CLI-susceptible strains (5 emm1 strains, 6 emm3 strains, 3 emm4 strains, 1 emm6 strain, 3 emm12 strains, 1 emm28 strain, and 4 emm89 strains), and 19 of the 23 strains showed similar NADase induction phenotypes to that shown in strain 1529. These results indicate that NADase induction by CLI treatment is not restricted to specific strains and it could be a standard phenotype among CLI-susceptible S. pyogenes strains. We also analyzed four CLI-resistant strains. All four strains showed increased extracellular NADase activities at high concentrations of CLI that did not inhibit bacterial growth. These results indicated that the subinhibitory dose of CLI was not the critical factor for NADase induction.